The markers to predict the response to neoadjuvant therapy in patients with rectal cancer - mei, Jiang Shu; Yan, Hongjiang; Jin, Linzhi; Dou, Xue; Chen, Dong; Xu, Xiaoqing; Guo, Hongliang; Mu, Dianbin; Wang, Renben (JOURNAL OF ADVANCES IN PHYSICS, 2015)
Locally advanced rectal cancer is currently treated with preoperative radiochemotherapy, but the response is not uniform. Most patients benefit from preoperative CRT, however, a small proportion of a patient population is less likely to respond to the treatment. The purpose of this study was to measure neoadjuvant therapy combined with Ki-67 and VEGF expression in pretreatment biopsies and postoperative specimensï¼Œserum carcinoembryonic antigen (CEA) and CA19-9 level from patients with locally advanced rectal cancer receiving intensive neoadjuvant treatment and to correlate the findings with clinical outcome.